Association of serum Klotho with the severity and mortality among adults with cardiovascular-kidney-metabolic syndrome - Jiao Tang; Zhehao Xu; Li Ren; Jiahua Xu; Xin Chen; Yian Jin; Ruiyun Liang; Huanji Zhang (Lipids in Health and Disease)
Abstract Background Cardiovascular-kidney-metabolic (CKM) syndrome is characterized as a systemic disease resulting from the pathophysiological interplay among metabolic risk factors, chronic kidney disease (CKD), and cardiovascular disease (CVD). The Klotho protein may serve as a novel biomarker. However, the utility of serum Klotho levels as an indicator of severity and mortality risk in CKM syndrome remains uncertain. Methods This study involved 9,871 participants from the National Health and Nutrition Examination Survey (NHANES) conducted between 2007 and 2016. Serum Klotho levels were measured using an enzyme-linked immunosorbent assay kit. The optimal cutoff value was established through the maximum Youden’s index. Multivariable weighted regression models were employed to calculate the odds ratio and hazard ratio, along with the 95% confidence interval, to evaluate the association between serum Klotho levels and the severity of CKM syndrome, as well as all-cause and cardiovascular mortality. Additionally, the receiver operating characteristic curve and restricted cubic spline curves were utilized to assess predictive efficacy and to explore nonlinear relationships. Results After adjusting for potential confounding factors, a non-linear relationship was seen between the Klotho protein, and CKM syndrome. In the multivariable, piecewise logistic regression, when the Serum klotho was less than 801, the risk of CKM syndrome decreased with the increase in Serum klotho (OR = 0.82, 95%CI 0.70, 0.96; p < 0.001). Furthermore, we observed the association when the Serum klotho was greater than 801 (OR = 0.94, 95%CI 0.89, 0.99; p = 0.035). The relationship between serum Klotho levels and all-cause mortality was U-shaped, while the relationship with cardiovascular mortality was L-shaped. Specifically, low serum Klotho levels were associated with an increase in all-cause mortality by 21% and cardiovascular mortality by 76% among patients with CKM syndrome. Furthermore, serum Klotho levels demonstrated excellent predictive efficacy for both the severity and mortality associated with CKM syndrome. Conclusions This study indicates that low serum Klotho levels serve as reliable indicators of both the severity of CKM syndrome and the associated risk of mortality.